ENVIRONMENTAL LITERACY OF JUNIOR HIGH SCHOOL STUDENTS IN BOGOR: CONTRIBUTION OF KNOWLEDGE TO ENVIRONMENTAL ATTITUDES AND BEHAVIORS - Nadila Fetiana; Anna Permanasari; Irvan Permana (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to analyze students' environmental literacy levels through survey methods and determine the relations between each environmental literacy indicator. The research sample was 80 junior high school students in Bogor. The collection technique was carried out using environmental literacy instruments adapted from the Middle Schools Environmental Literacy Survey/Instrument (MSELS/I) questions by NELA with modifications to the context of environmental pollution. Data acquisition was transformed and interpreted using the NELA transformation method. The results showed that students' environmental literacy was still low; knowledge (23.2%) is in the medium category, cognitive skills (11.4%) are in the low category, environmental attitudes (40.8%) is in the medium category and environmental behavior (22.2%) is in the low category with the results of achieving the entire student literacy domain of 97.8 (low). The results of further research show that there is a relation between knowledge and attitudes, knowledge with behavior, and attitudes with behavior, and there is no relation between cognitive skills and knowledge, attitudes and behaviors. A considerable contribution from other factors that affect each indicator of environmental literacy will be a chance for follow up research.